The turning pointe - Torres, Vanessa L. (Alfred A. Knopf, 2022)
"In 1980s Minnesota, when auditions for a concert with Prince are announced, 16-year-old Rosa Dominguez, the daughter of a tyrant ballet master, is desperate to escape her pointe shoes and show everyone what she can do"--